TINJAUAN AKUSTIK PERANCANGAN INTERIOR GEDUNG PERTUNJUKAN - Ambarwati, Dwi Retno Sri (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Many factors must be considered in the planning of the acoustic of interior auditorium according to its function, so that the performance of the artists or actors can be caught better and the quality of the show is able to satisfy the audience. Especial conditions that must be fulfilled in the planning of the acoustic of interior auditorium are: enough loudness by shortening the distance of the audience with the sound, heightening the source of sound, the accompaniment of the floor, encircle the source of sound by the voice reflector, the dimension of room must match with the space volume, avoiding parallel sound reflector and locate the audiences in the beneficial area. Other conditions are the right form of space, energy of sound distribute into whole space, free from the handicaps of acoustic and the form treatment of floor, wall and plafond and also veneering them with the sound absorber material. Financial consideration usually represent the constrictor of the acoustic repair, because getting a good quality of acoustic cost a lot of money . Keyword: acoustics, auditorium, and interior building